Analisis Perceived Usefulness, Perceived Ease of Use dan Perceived Risk Terhadap Minat Penggunaan Pembayaran Digital Quick Response Indonesia Standard (QRIS) Pada Pelaku UMKM - Edwin Zusrony; Luthfy Purnanta Anzie; Pindo Asti; Gibson Manalu; Ivan Permana; Tri Imaliya (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The research aims to measure and determine the effect of perceived usefulness, perceived ease of use, and perceived risk on the interest in using QRIS digital payments by MSME actors in Salatiga City, Central Java Province. Data collection uses Google Forms with a Likert scale. The sample that will be used is 60 MSME respondents in the city of Salatiga with a non-probability sampling technique of the convenience sampling type, namely because of the ease of obtaining data. Data analysis used multiple linear regression methods and was processed using SPSS 26.0. The results of the study show that the variables perceived usefulness, perceived ease of use, and perceived risk have a significant influence on the interest in using QRIS digital payments by MSME actors in Salatiga City and the perceived usefulness variable has a dominant effect on the interest in using QRIS digital payments by MSME actors in Salatiga City, Central Java Province.